Systematic Review of Haze Impact in Kalimantan: Meta-Analysis of PM2.5 Exposure on Non-Communicable Diseases - Rika Aprianti; Muhammad Fachri; Nurmalisa Lusida (Journal of Noncommunicable Diseases Prevention and Control, 2025)
Background: Haze from peatland fires in Kalimantan represents a major public health threat contributing to increased non-communicable disease (NCD) burden via elevated PM2.5 exposure. This study aimed to conduct a systematic review of haze impacts in Kalimantan and a meta-analysis of PM2.5 exposure associations with NCD outcomes. Methods: Systematic review followed PRISMA 2020 guidelines. Searches were conducted in PubMed, Scopus, Google Scholar, and Indonesian journals (2010-2025) using keywords related to haze, Kalimantan, PM2.5, and NCDs. Observational studies reporting associations between haze/PM2.5 exposure and health outcomes were included. Meta-analysis employed random-effects models using R (meta package). Study quality was assessed via Newcastle-Ottawa Scale. Results: From 1,248 identified articles, 14 studies met inclusion criteria (8 for systematic review, 6 for meta-analysis). Haze exposure in Kalimantan increased respiratory clinic visits by 36.6% (95% CI: 10.2%-69.3%) during haze days. Meta-analysis revealed an 8.7% (95% CI: 6.2%-11.3%) increase in premature mortality risk and 12.4% (95% CI: 8.1%-17.0%) increase in cardiovascular hospitalization risk per 10 μg/m³ PM2.5 increment from fire sources. Moderate heterogeneity (I² = 58%). Annual burden estimates in Kalimantan: >3,200 excess deaths and >1,200 severe childhood asthma cases in Palangka Raya region alone during extreme fire years such as 2019. Conclusion: Haze in Kalimantan significantly elevates NCD burden, particularly respiratory and cardiovascular diseases, through high PM2.5 exposure. Urgent policies for peatland fire prevention, ecosystem restoration, and early warning systems are needed to control NCDs in the region. Midwifery academies play a vital role in environmental health education for communities.